Charipines from Colombia (Hymenoptera: Figitidae), with the description of two new species - FERRER-SUAY, MAR; SELFA, JESÚS; PUJADE-VILLAR, JULI (Revista Colombiana de Entomología, 2012)
The fauna of Figitidae (Hymenoptera: Figitidae) present in Colombia was studied from collections made with Malaise traps by the Humboldt Institute in several places of Colombia thanks to the project “Biodiversidad Insectos de Colombia” over the years 2000-2004. A total of eight species was identified. Six species were cited for the first time in the country: Alloxysta arcuata, A. castanea, A. hansoni, A. obscurata, A. pilipennis and Phaenoglyphis villosa. Two new species are described: Alloxysta medinae n. sp. and Alloxysta torresi n. sp. Two species are cited for the first time from a neotropical region: Alloxysta obscurata and A. pilipennis; and A. arcuata, A. castanea and A. pilipennis are cited for the first time from the American continent. A key is included for the identification of the species present in Colombia. The geographic distribution of some Palearctic species is broadened.